THE The Human and the Non-Human in Ze života hmyzu by the Brothers Čapek: Contexts, Scheme, Interpretation - Kudlová, Klára (Porównania, 2021)
The study „The mutual engagement of human and insect sphere in Čapeks´ most-played drama“ attempts at a contextual perspective on the human and natural spheres of Čapeks celebrated „insect play“ (Ze života hmyzu). Summing up the potential thematic and structural influences on the play (such as L´Oiseau Bleu), the study uncovers the structure of the play (the mise-en-abyme and circular composition) and proves it to be one of the key interpretative tools for its understanding. The other analytical tools are derived from detailed evaluation of the figure of the Tramp (a universal human figure) and of the individual insect groups (types). In the final search for the core dynamics and the message of the play, the influence and legacy of Jean-Henri Fabre is recalled, alongside the authors´ own perspective.